Plant Growth Promoting Microbes in the Future Management of Indonesian Estate Forests - Gafur, Abdul (KnE Life Sciences, 2022)
Plant growth promoting microbes (PGPM) are soil-borne microbes that colonize plant internal tissues as endophytes or live on root surfaces. They are classified into three main groups based on their growth promoting mechanisms, namely biofertilizers, biostimulants, and biocontrol agents, each of which contribute directly or indirectly to improved plant growth and productivity in a variety of ecosystems. PGPM development as biocontrol agents in the context of integrated pest and disease management has been a research program initiative in several forestry companies for quite some time. Adoption of PGPM as biofertilizers and/or biostimulants, particularly in nursery operations to produce vigorous and healthy seedlings, has recently gained traction. The current state and potential future roles of PGPM in the sustainable production of Indonesian estate forests are discussed in this paper. Keywords: Acacia; biocontrol agent; biofertilizer; biostimulant; Eucalyptus